Pengaruh Implementasi Model Quantum Teaching dalam Meningkatkan Hasil Belajar IPS di SMPN 1 Bantaran, Probolinggo - Maulani, Ma’rifatul Jannah; Sutomo, Moh. (Jurnal Penelitian dan Pendidikan IPS, 2025)
One of the main challenges in education today is the low motivation to learn among students. Many learners feel less enthusiastic about participating in classroom learning processes. This is partly caused by monotonous learning activities, where the teaching methods used lack variety and innovation. Often, the learning process is still dominated by one-way lecturing methods, causing students to become passive listeners with little opportunity to actively engage in learning. As a result, students feel bored and less challenged to develop their potential and creativity. The aim of this research is to encourage students to be more active in the learning process as well as to build a comfortable learning atmosphere that is supportive and emotionally positive, so that students feel safe and able to express themselves during learning. A comfortable learning environment enables students to maximize their learning potential and improve their learning outcomes as reflected in their academic performance. This research uses a quantitative approach with a pre-experimental design, specifically the One Group Pre-test and Post-test design. The subjects in this study were seventh-grade students at SMPN 1 Bantaran, selected using Simple Random Sampling (CRS) technique. From the randomization, class VII-A was chosen as the sole sample, consisting of 28 students. Learning outcome data were collected through a multiple-choice test consisting of 20 items, which had previously undergone validity, reliability, difficulty level, discrimination power, and distractor effectiveness tests using Anates V4 software. Data analysis techniques included normality test, homogeneity test, and Paired Sample t-test using SPSS version 25 for Windows, to determine whether there was a significant effect of the implementation of the Quantum Teaching model on student learning outcomes. The results showed that there was a significant effect from the Quantum Teaching model. Data analysis using the Paired Sample t-test showed a significance value of 0.000, which is below the threshold of 0.05. This finding indicates a significant difference between learning outcomes before and after the implementation of the model. Thus, it can be concluded that the implementation of the Quantum Teaching model has a significant effect on improving student learning outcomes, particularly in Social Studies subjects at SMPN 1 Bantaran